Fe oxides control the vulnerability of paddy soils to microplastic-induced carbon loss - Xiaonan Lu; Yao Yao; Lukas Van Zwieten; Lili Wang; Tida Ge; Olga Shibistova; Georg Guggenberger (Journal of Environmental Chemical Engineering, 2026)

Microbial community composition in degraded Alaskan permafrost soils: implications of distinct hydrological conditions for enzymatic activity and extracellular polymeric substances content - Muhammad Waqas; Patrick Liebmann; Cordula Vogel; Milan Varsadiya; Haitao Wang; Olga Shibistova; Milan Novák; Tim Urich; Georg Guggenberger; Jiří Bárta (Polar Biology, 2026)

Nitrogen and phosphorus fertilisation suppresses litter mineralisation but sustains positive priming in semi-arid agricultural soil - Yuhuai Liu; Heng Wang; Xiantao Ai; Olga Shibistova; Tida Ge; Yongfu Li; Georg Guggenberger (Plant and Soil, 2026)

Stick together: isolation and characterization of exopolysaccharides producing psychrotolerant bacteria from Alaskan permafrost soils - Muhammad Waqas; Simona Zelenková; Cordula Vogel; Broder Rühmann; Milan Varsadiya; Patrick Liebmann; Haitao Wang; Olga Shibistova; Tim Urich; Georg Guggenberger; Jiří Bárta (Polar Biology, 2025)

Wind erosion after steppe conversion in Kazakhstan - Moritz Koza; Roger Funk; Julia Pöhlitz; Christopher Conrad; Olga Shibistova; Tobias Meinel; Kanat Akshalov; Gerd Schmidt (Soil and Tillage Research, 2024)

Microbial response on changing C:P stoichiometry in steppe soils of Northern Kazakhstan - Yuhuai Liu; Olga Shibistova; Guan Cai; Leopold Sauheitl; Mouliang Xiao; Tida Ge; Georg Guggenberger (Plant and Soil, 2023)

C:N:P stoichiometry regulates soil organic carbon mineralization and concomitant shifts in microbial community composition in paddy soil - Xiaomeng Wei; Zhenke Zhu; Yi Liu; Yu Luo; Yangwu Deng; Xingliang Xu; Shoulong Liu; Andreas Richter; Olga Shibistova; Georg Guggenberger; Jinshui Wu; Tida Ge (Biology and Fertility of Soils, 2020)

Temperature response of permafrost soil carbon is attenuated by mineral protection - Norman Gentsch; Birgit Wild; Robert Mikutta; Petr Čapek; Katka Diáková; Marion Schrumpf; Stephanie Turner; Cynthia Minnich; Frank Schaarschmidt; Olga Shibistova; Jörg Schnecker; Tim Urich; et al. (Global Change Biology, 2018)
Climate change in Arctic ecosystems fosters permafrost thaw and makes massive amounts of ancient soil organic carbon ( OC ) available to microbial breakdown. However, fractions of the organic matter ( OM ) may be protected from rapid decomposition by their association with minerals. Little is known about the effects of mineral‐organic associations ( MOA ) on the microbial accessibility of OM in permafrost soils and it is not clear which factors control its temperature sensitivity. In order to investigate if and how permafrost soil OC turnover is affected by mineral controls, the heavy fraction ( HF ) representing mostly MOA was obtained by density fractionation from 27 permafrost soil profiles of the Siberian Arctic. In parallel laboratory incubations, the unfractionated soils (bulk) and their HF were comparatively incubated for 175 days at 5 and 15°C. The HF was equivalent to 70 ± 9% of the bulk CO 2 respiration as compared to a share of 63 ± 1% of bulk OC that was stored in the HF . Significant reduction of OC mineralization was found in all treatments with increasing OC content of the HF ( HF ‐ OC ), clay‐size minerals and Fe or Al oxyhydroxides. Temperature sensitivity (Q10) decreased with increasing soil depth from 2.4 to 1.4 in the bulk soil and from 2.9 to 1.5 in the HF . A concurrent increase in the metal‐to‐ HF ‐ OC ratios with soil depth suggests a stronger bonding of OM to minerals in the subsoil. There, the younger 14 C signature in CO 2 than that of the OC indicates a preferential decomposition of the more recent OM and the existence of a MOA fraction with limited access of OM to decomposers. These results indicate strong mineral controls on the decomposability of OM after permafrost thaw and on its temperature sensitivity. Thus, we here provide evidence that OM temperature sensitivity can be attenuated by MOA in permafrost soils.

Fate of rice shoot and root residues, rhizodeposits, and microbial assimilated carbon in paddy soil - part 2: turnover and microbial utilization - Zhenke Zhu; Tida Ge; Yajun Hu; Ping Zhou; Tingting Wang; Olga Shibistova; Georg Guggenberger; Yirong Su; Jinshui Wu (Plant and Soil, 2017)

Rice rhizodeposition and carbon stabilisation in paddy soil are regulated via drying-rewetting cycles and nitrogen fertilisation - Cornelius Talade Atere; Tida Ge; Zhenke Zhu; Chengli Tong; Davey L. Jones; Olga Shibistova; Georg Guggenberger; Jinshui Wu (Biology and Fertility of Soils, 2017)

Phosphorus content as a function of soil aggregate size and paddy cultivation in highly weathered soils - Baozhen Li; Tida Ge; Heai Xiao; Zhenke Zhu; Yong Li; Olga Shibistova; Shoulong Liu; Jinshui Wu; Kazuyuki Inubushi; Georg Guggenberger (Environmental Science and Pollution Research, 2016)

Aspect-vegetation complex effects on biochemical characteristics and decomposability of soil organic carbon on the eastern Qinghai-Tibetan Plateau - Ning-Ning Zhao; Georg Guggenberger; Olga Shibistova; Dao Thi Thao; Wen Jing Shi; Xiao Gang Li (Plant and Soil, 2014)

Landscape controls of CH 4 fluxes in a catchment of the forest tundra ecotone in northern Siberia - HEINER FLESSA; ANDREJ RODIONOV; GEORG GUGGENBERGER; HANS FUCHS; PAUL MAGDON; OLGA SHIBISTOVA; GALINA ZRAZHEVSKAYA; NATALIA MIKHEYEVA; OLEG A. KASANSKY; CHRISTIAN BLODAU (Global Change Biology, 2008)
Terrestrial ecosystems in northern high latitudes exchange large amounts of methane (CH 4 ) with the atmosphere. Climate warming could have a great impact on CH 4 exchange, in particular in regions where degradation of permafrost is induced. In order to improve the understanding of the present and future methane dynamics in permafrost regions, we studied CH 4 fluxes of typical landscape structures in a small catchment in the forest tundra ecotone in northern Siberia. Gas fluxes were measured using a closed‐chamber technique from August to November 2003 and from August 2006 to July 2007 on tree‐covered mineral soils with and without permafrost, on a frozen bog plateau, and on a thermokarst pond. For areal integration of the CH 4 fluxes, we combined field observations and classification of functional landscape structures based on a high‐resolution Quickbird satellite image. All mineral soils were net sinks of atmospheric CH 4 . The magnitude of annual CH 4 uptake was higher for soils without permafrost (1.19 kg CH 4 ha −1 yr −1 ) than for soils with permafrost (0.37 kg CH 4 ha −1 yr −1 ). In well‐drained soils, significant CH 4 uptake occurred even after the onset of ground frost. Bog plateaux, which stored large amounts of frozen organic carbon, were also a net sink of atmospheric CH 4 (0.38 kg CH 4 ha −1 yr −1 ). Thermokarst ponds, which developed from permafrost collapse in bog plateaux, were hot spots of CH 4 emission (approximately 200 kg CH 4 ha −1 yr −1 ). Despite the low area coverage of thermokarst ponds (only 2.1% of the total catchment area), emissions from these sites resulted in a mean catchment CH 4 emission of 3.8 kg CH 4 ha −1 yr −1 . Export of dissolved CH 4 with stream water was insignificant. The results suggest that mineral soils and bog plateaux in this region will respond differently to increasing temperatures and associated permafrost degradation. Net uptake of atmospheric CH 4 in mineral soils is expected to gradually increase with increasing active layer depth and soil drainage. Changes in bog plateaux will probably be much more rapid and drastic. Permafrost collapse in frozen bog plateaux would result in high CH 4 emissions that act as positive feedback to climate warming.

Storage and mobility of black carbon in permafrost soils of the forest tundra ecotone in Northern Siberia - GEORG GUGGENBERGER; ANDREJ RODIONOV; OLGA SHIBISTOVA; MATTHIAS GRABE; OLEG A. KASANSKY; HANS FUCHS; NATALIA MIKHEYEVA; GALINA ZRAZHEVSKAYA; HEINER FLESSA (Global Change Biology, 2008)
Boreal permafrost soils store large amounts of organic carbon (OC). Parts of this carbon (C) might be black carbon (BC) generated during vegetation fires. Rising temperature and permafrost degradation is expected to have different consequences for OC and BC, because BC is considered to be a refractory subfraction of soil organic matter. To get some insight into stocks, variability, and characteristics of BC in permafrost soils, we estimated the benzene polycarboxylic acid (BPCA) method‐specific composition and storage of BC, i.e. BPCA‐BC, in a 0.44 km 2 ‐sized catchment at the forest tundra ecotone in northern Siberia. Furthermore, we assessed the BPCA‐BC export with the stream draining the catchment. The catchment is composed of various landscape units with south‐southwest (SSW) exposed mineral soils characterized by thick active layer or lacking permafrost, north‐northeast (NNE) faced mineral soils with thin active layer, and permafrost‐affected raised bogs in plateau positions showing in part thermokarst formation. There were indications of vegetation fires at all landscape units. BC was ubiquitous in the catchment soils and BPCA‐BC amounted to 0.6–3.0% of OC. This corresponded to a BC storage of 22–3440 g m −2 . The relative contribution of BPCA‐BC to OC, as well as the absolute stocks of BPCA‐BC were largest in the intact bogs with a shallow active layer followed by mineral soils of the NNE aspects. In both landscape units, a large proportion of BPCA‐BC was stored within the permafrost. In contrast, mineral soils with thick active layer or lacking permafrost and organic soils subjected to thermokarst formation stored less BPCA‐BC. Permafrost is, hence, not only a crucial factor in the storage of OC but also of BC. In the stream water BPCA‐BC amounted on an average to 3.9% of OC, and a yearly export of 0.10 g BPCA‐BC m −2 was calculated, most of it occurring during the period of snow melt with dominance of surface flow. This suggests that BC mobility in dissolved and colloidal phase is an important pathway of BC export from the catchment. Such a transport mechanism may explain the high BC concentrations found in sediments of the Arctic Ocean.

Intermittent low temperatures constrain spring recovery of photosynthesis in boreal Scots pine forests - Ingo Ensminger; Dmitry Sveshnikov; Douglas A. Campbell; Christiane Funk; Stefan Jansson; Jon Lloyd; Olga Shibistova; Gunnar Öquist (Global Change Biology, 2004)
During winter and early spring, evergreen boreal conifers are severely stressed because light energy cannot be used when photosynthesis is pre‐empted by low ambient temperatures. To study photosynthetic performance dynamics in a severe boreal climate, seasonal changes in photosynthetic pigments, chloroplast proteins and photochemical efficiency were studied in a Scots pine forest near Zotino, Central Siberia. In winter, downregulation of photosynthesis involved loss of chlorophylls, a twofold increase in xanthophyll cycle pigments and sustained high levels of the light stress‐induced zeaxanthin pigment. The highest levels of xanthophylls and zeaxanthin did not occur during the coldest winter period, but rather in April when light was increasing, indicating an increased capacity for thermal dissipation of excitation energy at that time. Concomitantly, in early spring the D1 protein of the photosystem II (PSII) reaction centre and the light‐harvesting complex of PSII dropped to their lowest annual levels. In April and May, recovery of PSII activity, chloroplast protein synthesis and rearrangements of pigments were observed as air temperatures increased above 0°C. Nevertheless, severe intermittent low‐temperature episodes during this period not only halted but actually reversed the physiological recovery. During these spring low‐temperature episodes, protective processes involved a complementary function of the PsbS and early light‐induced protein thylakoid proteins. Full recovery of photosynthesis did not occur until the end of May. Our results show that even after winter cold hardening, photosynthetic activity in evergreens responds opportunistically to environmental change throughout the cold season. Therefore, climate change effects potentially improve the sink capacity of boreal forests for atmospheric carbon. However, earlier photosynthesis in spring in response to warmer temperatures is strongly constrained by environmental variation, counteracting the positive effects of an early recovery process.

Air temperature triggers the recovery of evergreen boreal forest photosynthesis in spring - Suni Tanja; Frank Berninger; Timo Vesala; Tiina Markkanen; Pertti Hari; Annikki Mäkelä; Hannu Ilvesniemi; Heikki Hänninen; Eero Nikinmaa; Timo Huttula; Tuomas Laurila; Mika Aurela; et al. (Global Change Biology, 2003)
The timing of the commencement of photosynthesis ( P * ) in spring is an important determinant of growing‐season length and thus of the productivity of boreal forests. Although controlled experiments have shed light on environmental mechanisms triggering release from photoinhibition after winter, quantitative research for trees growing naturally in the field is scarce. In this study, we investigated the environmental cues initiating the spring recovery of boreal coniferous forest ecosystems under field conditions. We used meteorological data and above‐canopy eddy covariance measurements of the net ecosystem CO 2 exchange ( NEE ) from five field stations located in northern and southern Finland, northern and southern Sweden, and central Siberia. The within‐ and intersite variability for P * was large, 30–60 days. Of the different climate variables examined, air temperature emerged as the best predictor for P * in spring. We also found that ‘soil thaw’, defined as the time when near‐surface soil temperature rapidly increases above 0°C, is not a useful criterion for P * . In one case, photosynthesis commenced 1.5 months before soil temperatures increased significantly above 0°C. At most sites, we were able to determine a threshold for air‐temperature‐related variables, the exceeding of which was required for P * . A 5‐day running‐average temperature ( T 5 ) produced the best predictions, but a developmental‐stage model ( S ) utilizing a modified temperature sum concept also worked well. But for both T 5 and S , the threshold values varied from site to site, perhaps reflecting genetic differences among the stands or climate‐induced differences in the physiological state of trees in late winter/early spring. Only at the warmest site, in southern Sweden, could we obtain no threshold values for T 5 or S that could predict P * reliably. This suggests that although air temperature appears to be a good predictor for P * at high latitudes, there may be no unifying ecophysiological relationship applicable across the entire boreal zone.